Investigation of Obesity, Physical Activity and Sedentary Behaviors of Individuals with and Without Autism Spectrum Disorder during the Covid-19 Pandemic Process - Nevzat DEMİRCİ; Diajeng Tyas Pinru Phytanza (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2021)
Adolescents with autism spectrum disorder (ASD) may be at higher risk compared to their typically developing peers. In this study, it was aimed to compare individuals with and without autism spectrum disorder affected by the Covid-19 pandemic process with their peers in terms of obesity, physical activity and sedentary behaviors. Methods: 64 individuals with ASD and 78 healthy individuals were included in the study. An online questionnaire consisting of sociodemographic data, BMI, physical activity and sedentary behavior habits was applied to the participants. Results: Adolescents with autism spectrum disorders were found to be less physically active and more likely to be overweight and obese compared to their typically developing peers (0.001***). BMI (kg/m2) increased compared to before Covid-19. Sedentary behavior increased during quarantine (0.001***). Participation in physical activity decreased in individuals with autism spectrum disorder. As a result: shows the need for targeted programs to reduce unhealthy weight status and support physical activity opportunities for adolescents with autism spectrum disorders.Keywords: Autism Spectrum Disorder, COVID-19, Obesity, physical activity, Sedentary Behaviors